INVESTASI BODONG DI PASAR MODAL SYARIAH INDONESIA: STUDI KASUS DAN LANGKAH PREVENTIF BAGI INVESTOR PEMULA - Ariska, Ayu; Aulia Fitri, Nur; Hidayat, Rahmat; Fakhri Amir, Muhammad; Kamiruddin, Kamiruddin (Politeknik Bisnis Indonesia, 2024)
This research aims to identify the characteristics of fraudulent investments, explore well-known cases of fraudulent investments in Indonesia, and present preventive measures for novice investors to avoid the pitfalls of these illegal investments. The research method used is a literature study by collecting and analysing data from various primary and secondary sources, including Islamic finance literature, investigation reports, and case studies. The results show that fraudulent investments often use Ponzi schemes, where funds from new investors are used to pay profits to older investors. High-profile cases such as First Travel, Net89, and Pandawa Cooperative illustrate how these schemes harm many people. Suggested preventive measures include improving financial literacy, consulting with financial experts, and choosing investments that have legality and official licences.